Dividen dan Volatilitas Harga Saham saat PSBB di Indonesia : Peran Moderasi Cash Holding - Pratadina, Aura; Salma, Dini Kamilia (E-Jurnal Akuntansi; Vol 32 No 11 (2022), 2022)
The Large-Scale Social Restrictions Policy (PSBB) as an effort to deal with Covid 19 in Indonesia, has weakened the JCI and triggered share price volatility. Companies use cash holdings to strengthen the ability of dividends to reduce share price volatility for a sustainable negative impact on the company. The aim of the research is to provide empirical evidence of the moderating role of cash holding on the relationship between dividends and share price volatility after the PSBB in Indonesia. The research population is all non-financial companies listed on the IDX in 2020, with a final sample of 223 companies, which were analyzed using moderated regression analysis (MRA). The results of the study show that when the business environment is uncertain due to PSBB, cash holding shows that companies are careful in using cash, creates positive sentiment from investors, strengthens positive signals formed by dividends and reduces price volatility in the capital market. Keywords: Dividends; Volatility Stock Price; Cash Holding; Covid 19